Exploring the Effects of Retro Walking on Functional Outcomes in Knee Osteoarthritis: A Scoping Review - Putri Satrio, Alifia Azzahra; Rahman, Farid (UNIB Press, 2024)
Retro walking is a form of exercise that involves walking backwards as an alternative to forward walking. Previous studies highlighted its benefits in improving balance, coordination, and muscle strength, therefore improving functional ability of the lower extremities including the knee joints. This review aims to provide overview of the latest available studies regarding the impact of retro walking in patients with knee osteoarthritis. Studies that had been published until October 2023 in a peer-reviewed journal with the language limited to English and Indonesian were considered. The intervention was retro walking as an adjunct exercise program, and the outcome was aspects related to functional ability of the knee. After reviewing 20 included articles, it was found that the duration of retro walking exercise was generally given for 10 minutes per session for a total of about 70 minutes per week to patients with knee osteoarthritis 40 years old and over, with the exercise given using treadmill, with or without harness, or simply on the ground with cone with various distance and the patients’ comfortable walking speed. The findings suggest that retro walking is effective as an adjunct to rehabilitation program for the improvement of aspects that may eventually help improve and maintain functional abilities of knee osteoarthritis patients.